The use of websites by students of the Faculty of Management and Economics at the Lebanese Lebanese University / Erbil - Jawad Mohammed Amin Issa Al Harki (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
Modern technological developments in the mid-1990s brought about a quantum leap and a real revolution in the world of communication and the Internet spread throughout the globe, connecting parts of this world with its wide space, paving the way for all societies to converge and to exchange ideas, ideas, and desires. A web browser of the multimedia available in it, and became the best way to achieve communication between individuals and groups, and then emerged websites, which became a scientific encyclopedia that serves all users in all fields, such as scientific research, In all its aspects, and the governmental domain in all its forms and forms, in addition to electronic publishing. This study aims to monitor and analyze the motives of the use of students of the Faculty of Administration and Economics at the Lebanese French University for websites. The study used the survey methodology. The study relied on the survey paper as a tool for collecting the required data, which included a set of questions to reach the objectives of the current study. The sample of the field study was a random sample of the students of the Faculty of Administration and Economics at the Lebanese French University. The sample size of the study was (200) distributed equally among the male and female members, where (100) for male and (100) for females. Further, the most important results of the study that in that at the beginning of the emerging of websites used and followed by students of the Faculty of Administration and Economics, entertainment to spend their free time, and that the most sites used by the sample study was Face book.